Activation of PI3K/AKT/mTOR Pathway Causes Drug Resistance in Breast Cancer - Dong, Chao; Wu, Jiao; Chen, Yin; Nie, Jianyun; Chen, Ceshi (Frontiers in Pharmacology, 2021)
Although chemotherapy, targeted therapy and endocrine therapy decrease rate of disease recurrence in most breast cancer patients, many patients exhibit acquired resistance. Hyperactivation of the PI3K/AKT/mTOR pathway is associated with drug resistance and cancer progression. Currently, a number of drugs targeting PI3K/AKT/mTOR are being investigated in clinical trials by combining them with standard therapies to overcome acquired resistance in breast cancer. In this review, we summarize the critical role of the PI3K/AKT/mTOR pathway in drug resistance, the development of PI3K/AKT/mTOR inhibitors, and strategies to overcome acquired resistance to standard therapies in breast cancer.